Translating fraternity. Revolutionary Lexicon and Practices in the Italy of the Triennium (1796-1799) (Il Risorgimento. Rivista di storia moderna e contemporanea, 2024)
Fraternity is an idea and a way of being in history that finds an original expression in the French Revolution. Throughout this period, fraternity had been a bond capable of holding democrats together, endowing them with an indomitable virtue: a unity of hearts and principles. It proved to be a connection even more vital than politics in the society building process. In the Italy liberated by Bonaparte’s army, the meaning of fraternity underwent a transformation, evolving into a patriotic motive, into a concrete practice of democracy (fraternisation), into a load-bearing element of new social institutions. Thus, while liberty and equality were brought by Bonaparte, fraternity becomes distinctly Italian.